2016
DOI: 10.1111/ctr.12729
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre‐operative statin use on risk of mortality and early atrial fibrillation after heart transplantation

Abstract: Pre-operative statin therapy does not seem to influence the risk of mortality or early post-operative AF after HT. Future large-scale studies are required to validate these preliminary findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The final analysis included 18 articles, including 2 study cohorts from clinical trials and 16 cohort studies with 5393 heart transplant recipients were enrolled. The literature retrieval, review, and selection process are demonstrated in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final analysis included 18 articles, including 2 study cohorts from clinical trials and 16 cohort studies with 5393 heart transplant recipients were enrolled. The literature retrieval, review, and selection process are demonstrated in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The literature retrieval, review, and selection process are demonstrated in Figure . The characteristics and quality assessment of the included studies are presented in Table …”
Section: Resultsmentioning
confidence: 99%
“…However, data on the influence of pre-operative statin therapy in heart transplant surgery are lacking. A recent retrospective study on the influence of pre-transplant statin treatment on clinical outcomes after heart transplantation indicated that pre-operative statin therapy does not seem to influence the risk of mortality or early POAF after heart transplantation (Krishnan et al, 2016). These are preliminary findings, which should be confirmed by further large-scale prospective clinical studies.…”
Section: Statins In Postoperative Afmentioning
confidence: 89%